Handling of Tofu Liquid Waste in Central Sokaraja Village, Banyumas Regency - Hariadi Kadarisman (Faculty of Law Universitas Muhammadiyah Purwokerto, 2021)
Pollution of water, air, soil, and disposal of hazardous and toxic materials (B3) is a problem that must be around communities living around industrial areas. One of the problems that occur due to human activities is air pollution at air sources because it receives a pollution load that exceeds its carrying capacity. Pollution that causes a decrease in water quality can come from waste. Tofu liquid waste pollution is one of the causes of environmental pollution and can cause disease to humankind and manage a wastewater treatment system based on the nature and character of the tofu wastewater itself. This research discusses handling tofu liquid waste handling in the Village of Central Sokaraja based on Law Number 32 of 2009 concerning Environmental Protection and Management (Perlindungan dan Pengelolaan Lingkungan Hidup, UUPPLH). This research approach method is normative juridical. The normative juridical method is carried out through literature studies that examine secondary data in the form of laws and regulations, court decisions, agreements, contracts, or other legal documents, research results, assessment results, and other references. The handling of liquid tofu waste is not going well in Hamlet Muntug and Hamlet Kauman, Central Sokara Village. Due to WWTP, whose construction and pump system are not under the WTP establishment standards, and the public awareness of the craftsmen who know about environmental awareness. Furthermore, WWTP must carry out a full assessment to handle industrial tofu waste and involve competent stakeholders in their fields. Furthermore, the Village Government of Sokaraja provides solutions and education to the surrounding community, especially those involved in industries related to environmental protection and management.Keywords: Handling, Tofu Liquid Waste, Pollution